Vegetable Freshness Perception in Dementia with Lewy Bodies and Alzheimer's Disease - Oishi, Yuka (Dement Geriatr Cogn Dis Extra, 2020)
INTRODUCTION: Although various visual function deficits have been reported in patients with Alzheimer's disease (AD) and dementia with Lewy bodies (DLB), vegetable freshness perception has not been thoroughly examined. OBJECTIVE: To investigate vegetable freshness perception in patients with AD and DLB and to clarify the relationship between vegetable freshness perception and various visuoperceptual functions. METHODS: We enrolled 37 patients with probable DLB, 58 patients with probable AD, and 32 age-matched healthy controls. We assessed vegetable freshness perception and visuoperceptual functions, including vegetable brightness perception, contrast sensitivity, color perception, and stereopsis. Patients with DLB showed disproportionate deficits in vegetable freshness perception and vegetable luminance perception compared to patients with AD and controls. Analyses of the groups with higher and lower vegetable freshness perceptions revealed significant differences in contrast sensitivity and visual texture recognition. RESULTS: In the vegetable freshness test, we found significant differences among the 3 groups (F = 30.029, p < 0.0001); the extent of impairment in patients with DLB was greater than that in patients with AD. In patients with DLB, the vegetable freshness judgments were significantly correlated with texture judgment scores and contrast sensitivity. CONCLUSION: Our findings revealed significantly impaired vegetable freshness perception in patients with DLB. Vegetable freshness perception may be related to visual texture recognition in patients with DLB.